Edukasi terapi komplementer pada ibu hamil untuk mengurangi nyeri selama kehamilan - Fatimah, Sitti; Heriyana, Desi (JOURNAL of Public Health Concerns, 2026)
Background: Complementary therapy is a form of healing based on various modalities in health practices, supported by theory and belief. This therapy encompasses promotive, preventive, curative, and rehabilitative efforts, although currently, complementary therapy is an option during pregnancy to reduce common complaints or discomforts. Purpose: To provide knowledge and understanding of complementary therapies for health and their benefits to pregnant women during pregnancy. Method: This community service activity was held on October 25, 2025, from 9:30 to 11:00 a.m. WITA (Central Indonesian Time) at the Pajelele Village office, involving eight pregnant women as respondents. The material was delivered through interactive lectures, discussions, and demonstrations, accompanied by visual presentations and leaflets. The education materials covered complementary therapies and their health benefits during pregnancy. The activity was evaluated using pre-test and post-test questionnaires to measure changes in respondents' knowledge and understanding before and after the education. The data obtained were analyzed descriptively to illustrate differences in respondents' knowledge and understanding of complementary therapies from a pregnancy health perspective. The evaluation results are used as an indicator of activity effectiveness. Results: Data obtained on respondents' knowledge levels regarding complementary therapies and their benefits before the educational activity (pre-test) was 25.0% in the good category, 25.0% in the adequate category, and 50.0% in the poor category. Meanwhile, the level of knowledge of respondents after the educational activity (post-test) was 87.5% in the good category and 12.5% ​​in the adequate category. Conclusion: Health interventions that combine education (lectures) with direct demonstrations (practice/simulation) have proven highly effective in increasing pregnant women's knowledge and understanding of complementary therapies and their health benefits, thereby increasing motivation to implement them independently. Suggestion: It is hoped that educational activities accompanied by training on complementary therapies can be conducted regularly and involve health workers so that the public's understanding of the benefits of complementary therapies will be more fully understood based on medical knowledge. Keywords: Back pain; Complementary therapy; Health education; Pregnancy Pendahuluan: Terapi komplementer merupakan bentuk penyembuhan yang bersumber pada berbagai sistem modalitas dalam praktik kesehatan yang didukung oleh teori dan kepercayaan. Terapi tersebut meliputi upaya promotif, preventif, kuratif, dan rehabilitatif meskipun saat ini terapi komplementer yang ada menjadi salah satu pilihan selama kehamilan untuk mengurangi keluhan atau ketidaknyamanan yang umum terjadi Tujuan: Memberikan pengetahuan dan pemahaman tentang terapi komplementer untuk kesehatan dan manfaatnya kepada ibu hamil selama menjalani kehamilan. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan pada tanggal 25 Oktober 2025 pada pukul 09.30–11.00 wita di kantor Desa Pajelele dengan melibatkan 8 ibu hamil untuk menjadi responden. Materi disampaikan melalui ceramah interaktif, diskusi dan demonstrasi disertai media presentasi visual dan leaflet. Materi penyuluhan meliputi tentang terapi komplementer dan manfaat kesehatan selama masa kehamilan. Evaluasi kegiatan dilakukan menggunakan instrumen kuesioner pre-test dan post-test untuk mengukur perubahan tingkat pengetahuan dan pemahaman responden sebelum dan sesudah diberikan edukasi. Data yang diperoleh dianalisis secara deskriptif untuk menggambarkan perbedaan tingkat pengetahuan dan pemahaman responden tentang terapi komplementer dalam perspektif kesehatan kehamilan. Hasil evaluasi digunakan sebagai indikator efektivitas kegiatan.  Hasil: Mendapatkan data tingkat pengetahuan responden mengenai terapi komplementer dan manfaatnya sebelum kegiatan edukasi (pre-test) adalah sebesar 25.0% dalam kategori baik, sebesar 25.0% dalam kategori cukup, dan sebesar 50.0% dalam kategori kurang. Sedangkan tingkat pengetahuan responden setelah kegiatan edukasi (post-test) menjadi sebesar 87.5% dalam kategori baik dan sebesar 12.5% dalam kategori cukup. Simpulan: Intervensi kesehatan yang menggabungkan edukasi (ceramah) dengan demonstrasi langsung (praktik/simulasi) terbukti sangat efektif untuk meningkatkan pengetahuan dan pemahaman ibu hamil mengenai terapi komplementer dan manfaatnya dalam kesehatan, sehingga meningkatkan motivasi untuk menerapkan terapi secara mandiri. Saran: Diharapkan, kegiatan edukasi yang disertai dengan pelatihan tentang terapi komplementer dapat dilakukan secara berkala dan melibatkan tenaga kesehatan sehingga pemahaman tentang manfaat terapi komplementer akan lebih dirasakan oleh masyarakat berdasarkan ilmu pengetahuan medis.